Light, photoreceptors, and circadian clocks. - Foster, R; Hankins, M; Peirson, S (2007)
Research over the past decade has focused increasingly on the photoreceptor mechanisms that regulate the circadian system in all forms of life. Some of the results to emerge are surprising. For example, the rods and cones within the mammalian eye are not required for the alignment (entrainment) of circadian rhythms to the dawn-dusk cycle. There exists a population of directly light-sensitive ganglion cells within the eye that act as brightness detectors; these regulate both circadian rhythms and melatonin synthesis. An understanding of these "circadian photoreceptor" pathways, and the features of the light environment used for entrainment, have been and will continue to be heavily dependent on the appropriate use and measurement of light stimuli. Furthermore, if results from different laboratories, or species, are to be compared in any meaningful sense, standardized methods for light measurement and manipulation need to be adopted by circadian biologists. To this end, we describe light measurement in terms of both radiometric and photometric units and consider the appropriate use of light as a stimulus in circadian experiments. In addition, the construction of action spectra has been very helpful in associating photopigments with particular responses in a broad range of photobiological systems. Because the identity of the photopigments mediating circadian responses to light are often not known, we have also taken this opportunity to provide a step-by-step approach to conducting action spectra, including the construction of irradiance response curves, the calculation of relative spectral sensitivities, photopigment template fitting, and the underlying assumptions behind this approach. The aims of this chapter are to provide an accessible introduction to photobiological methods and explain why these approaches need to be applied to the study of circadian systems.